Experimental and computational evaluation of capacitive hyperthermia. (31st December 2022) - Beck, Marcus; Wust, Peter; Oberacker, Eva; Rattunde, Alexander; Päßler, Tom; Chrzon, Benjamin; Veltsista, Paraskevi Danai; Nadobny, Jacek; Pellicer, Ruben; Herz, Enrico; Winter, Lukas; Budach, Volker; et al.
Abstract: Objective: Hyperthermia as an enhancer of radio- and/or chemotherapy has been confirmed by various trials. Quite a few positive randomized trials have been carried out with capacitive hyperthermia systems (CHS), even though specific absorption rates (SAR) in deep regions are known to be inferior to the established annular-phased array techniques. Due to a lack of systematic SAR measurements for current capacitive technology, we performed phantom measurements in combination with simulation studies. Materials and Methods: According to the current guidelines, homogeneous and inhomogeneous agarose phantoms were manufactured for the commercial CHS Celsius42. Temperature/time curves were registered, and specific absorption rate (SAR) profiles and distributions were derived using the temperature gradient method. We implemented models for electrodes and phantom setups for simulation studies using Sim4Life. Results: For a standard total power of 200 W, we measured effective SAR until depths of 6–8 cm in a homogeneous phantom, which indicates fair heating conditions for tumor diseases in superficial and intermediate depths. A fat layer of 1 cm strongly weakens the SAR, but 10–20 W/kg are still achieved in intermediate to deep regions (2–10 cm). In the phantom setup with integrated bone, we measured low SAR of 5–10 W/kg in the cancellous bone. Our simulations could fairly describe the measured SAR distributions, but predict tendentially higher SAR than measured. Additional simulations suggest that we would achieve higher SAR with vital fatty tissue and bone metastases in clinical situations. Conclusion: Capacitive systems are suitable to heat superficial and medium-deep tumors as well as some bone metastases, and CHS application is feasible for a specific class of patients with pelvic and abdominal tumors. These findings are consistent with positive clinical studies.